Identity of Place in the Branding of Small and Medium-Sized Communes - Dudek-Mańkowska, Sylwia (Olsztyn Economic Journal, 2019)
The place brand is an extremely complex and multidimensional concept. Creation of a strong territorial brand is largely dependent on identifying aspects which define the attractiveness of a given place. As the literature on the subject and studies prepared by experts tend to devote a lot of attention to large urban centres, I decided to analyse how small and middle-sized local government units deal with the brand building process. The aim of the study was to determine the aspect of attractiveness that build identities of small and medium-sized communes (gminas), the dimensions of identities of such communes, and the typological classes of communes defined on the basis of these dimensions. Local authorities tend to perceive place brands primarily through the prism of key attributes of individual places. Natural attributes and attractions, geographical location, events, and sport facilities are the building blocks of attractiveness for small and middle-sized local government units. The key dimensions of the communes’ identities are the aspects of their attractiveness in terms of settlement, tourism and economic activity. The conducted analysis allowed also to distinguish communes with strong and distinctive identities, communes whose identities are defined primarily by their offer dedicated to the residents, ones defined most strongly by their business and cultural offers, communes whose identity is not very clear and requires intervention, as well as communes with a high level of tourist attractiveness and good recreational offerings.